Semiconductor substrate surface preparation using high temperature convection heating - HEALY, JR. JAMES; ADAMS, MICHAEL J; HOWLAND, JR. WILLIAM H (2005)
A method of processing a semiconductor wafer includes utilizing a heated gas to heat at least one part of a semiconductor wafer be convention whereupon at least one contaminant is desorbed therefrom. A stream of cooling gas is caused to pass over the one part of the semiconductor wafer in the absence of heated gas to cool the one part of the semiconductor wafer. A metrology tool is then caused to measure at least one part of the semiconductor wafer to determine at least one part of the semiconductor wafter to determine at least one characteristic thereof.